Job Performance Of Public Hospital Nurses: The Role Of Personal Resources, Job Resources And Work Engagement - Othman, Noraini (2012)

(untitled)
The aims of this study were to (a) examine the relationships between personal resources (psychological capital), job resources (social support, job characteristics), and job performance; and (b) investigate the effectiveness of work engagement as a mediator in the above relationships. Conservation of resources (COR) theory (Hobfoll, 1989) and Blau’s (1964) social exchange theory (SET) were utilized in developing the research framework. Job performance was operationalized as comprising of two broad dimensions: task performance and contextual performance.